2018
DOI: 10.1111/aor.13382
|View full text |Cite
|
Sign up to set email alerts
|

Computational analysis of customized cruciate retaining total knee arthroplasty restoration of native knee joint biomechanics

Abstract: The purpose of this study was to verify if customized prosthesis better preserves the native knee joint kinematics and provides lower contact stress on the polyethylene (PE) insert owing to the wider bone preservation than that of standard off-the-shelf prosthesis in posterior cruciate-retaining type total knee arthroplasty (TKA).Validated finite element (FE) models for were developed to evaluate the knee joint kinematics and contact stress on the PE insert after TKA with customized and standard off-the-shelf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Concerning knee kinematics, it has been reported that customized implants achieve kinematics that are more close to those of the native knee joint compared to off-the-shelf implants [ 90 92 ]. A study investigating contact stresses on the polyethyene using finite element models reported that customized implants had decreased contact stresses under gait cycle conditions [ 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…Concerning knee kinematics, it has been reported that customized implants achieve kinematics that are more close to those of the native knee joint compared to off-the-shelf implants [ 90 92 ]. A study investigating contact stresses on the polyethyene using finite element models reported that customized implants had decreased contact stresses under gait cycle conditions [ 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…A patient-specific TKA was developed using an existing 3D knee-joint model and the computed tomography (CT) and magnetic resonance imaging (MRI) of a healthy 36-year-old male with a normal knee condition (mechanical femoral tibial angle: varus 1°) [21,22,23,24,25]. The patient-specific TKA model was designed with actual anatomical geometries (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Yong‐Gon Koh et al of the Yonsei Sarang Hospital, Seoul, Republic of Korea assessed whether customized prosthesis better preserves the native knee joint kinematics and provides lower contact stress on the polyethylene (PE) insert owing to the wider bone preservation than that of standard off‐the‐shelf prosthesis in posterior cruciate‐retaining type total knee arthroplasty (TKA). Validated finite element models were developed to evaluate the knee joint kinematics and contact stress on the PE insert after TKA with customized and standard off‐the‐shelf (OTS) prostheses as well as in the normal healthy knee.…”
Section: Orthopedic Supportmentioning
confidence: 99%